Topic: Disability in person with schizophrenia: A study from north east India - Lavinia , A.M Lyngdoh (International Journal of Psychosocial Rehabilitation, 2025)
Schizophrenia is a significantly disabling disease that affects social .family psychological, vocational and occupational functioning. The present study aim to find the level of disability in person with schizophrenia .The research setting was at the Outpatient Department, LGB Regional Institute of Mental Health, Tezpur, Assam. Based on purposive sampling technique, samples of 60 subjects with diagnosis of schizophrenia were selected. Patients attending Outpatient Department for follow up in the age range between 18 to 60 years of both the gender were included. Patients with any organic involvement, who have any significant physical illness and with co morbid disorder were excluded.Socio-demographic and clinical data sheet, Positive and Negative Syndrome Scale [PANSS], Indian Disability Evaluation Assessment Scale [IDEAS]. In the present study it was found that majority of the respondents are having moderate level of disability [43%], while 40% are having mild level of disability, 15% are having severe level of disability and 1.7% of the respondents are having profound disability. Schizophrenia required a diverse range of interventions. Beside pharmacological intervention there is an equally vital psychosocial intervention are required in promoting independence, decreasing disability and enhancing quality of life in person with schizophrenia.